DETERMINING SMALL AND MEDIUM INDUSTRY MAIN PRODUCT IN BANYUMAS DISTRICT - Muhammad Unggul Abdul Fattah; Arief Satria; Gendut Suprayitno (Indonesian Journal of Business and Entrepreneurship (IJBE), 2016)
The purpose of this study was to determine the main product out of several alternative options of small and medium industries (IKM) main product in Banyumas District. The study was conducted by using in-depth interviews with respondents who were skillful experts with the authority to establish the main product in Banyumas. The criteria used in determining the main product come from 12 criteria set out in the Regulation of the Ministry of Home Affairs of Republic of Indonesia Number 9 of 2014. The establishment of criteria values was determined by using AHP and main product assessment with MPE. The results of the assessment indicate that the first priority of main product Banyumas is the coconut sugar. Coconut sugar products are supported by the abundance of natural resources of raw materials, while the other main product priorities include mendoan tempeh and getuk gerbong which are typical products of Banyumas. Both products are products that will facilitate economic growth through tourism as a specific sector for culinary products of Banyumas.Keywords: main product, small and medium industries (IKM), AHP, MPE